The impact of internal audit on operational risk management in the light of the performance standard for the practice of internal auditing: A field study on a number of private banks in the city of Erbil - Ahmed, Ramyar (Humanities Journal of University of Zakho, 2021)
This study aimed to identify the impact of internal auditing on operational risk management in accordance with international standards for the professional practice of internal auditing, including performance standards in private banks in the city of Erbil. It was distributed to (internal auditors, administrators, and managers), where the total number of distributed forms reached (120) forms, and (114) questionnaires valid for analysis were retrieved, which represents a return rate of approximately (95%).The researcher used the descriptive approach and the analytical approach in conducting this research, and where the research community was the auditing and management departments in some private banks in the city of Erbil (namely: Cihan Bank, Kurdistan Bank, and the Regional Commercial Bank RT), and the researcher used the statistical program (SPSS).), and appropriate statistical treatments in the analysis in this regard. Among the most important results of the study were: There is a positive statistical significance that shows the first hypothesis, which is (there is a significant relationship between the dimensions of internal auditing and risk management and between performance standards individually and collectively). There is a positive statistical significance that shows the second hypothesis, which is (there is a positive significant effect between the dimensions of internal auditing and risk management, and between performance standards individually and collectively, in other words,"what is the extent of the contribution of internal audit and operational risk management to the changes taking place in the dimensions of performance standards?”). There is a positive statistical significance that shows the third hypothesis, which is (weakness of strategic procedures, policies followed, the extent of awareness of the internal auditor) on performance standards. In light of the results, and the conclusions of this study, some proposals were put forward, the most important of which are: Giving more attention and care to the internal audit function in banking institutions. The necessity of creating a special department for risk management, so that it is flexible and effective in managing risks in banks. The necessity of the independence of the internal audit departments, and their coordination with the departments of risk management within banks, and attention to raising the qualifications of their employees. The banking institutions support the elements of the independence of the internal auditor so that he can carry out his duties to the fullest extent, especially with regard to risk management in accordance with special international standards.